Unequal pay for equal education! A case of gender wage gap from Punjab, Pakistan - Tirmazee, Zunia Saif (Publishing House of Wroclaw University of Economics and Business, 2023)
This study aimed to quantify the returns to tertiary educational attainment and measures the extent to which these returns differ for men and women. The article provides new empirical evidence of the returns to tertiary education literature by introducing a unique instrument, namely the supply of education to deal with endogeneity. The analysis is implemented using a pooled cross-section of five rounds of the Pakistan Social and Living Standards survey with 10,000 observations. The results show that the marginal returns to acquiring one extra year of education beyond matriculation are higher for women than for men. This result could partially explain the reversal of the gender gap in enrolments from secondary and lower to the post-secondary level of education in Punjab. The first stage results highlight the significance of investing in physical infrastructure for the greater accumulation of human capital.
Argumenta Oeconomica, 2023, Nr 1 (50), s. 67-93
Keywords: gender wage gap; returns; supply of education; tertiary education